DYNLL1 ubiquitinated and degraded by E3 ligase PRKN regulates cell cycle arrest and apoptosis in lung adenocarcinoma cells - Hongjie Tang; Changjiang Wei (Discover Oncology)
Abstract This study was intended to investigate the role of DYNLL1 in lung adenocarcinoma (LUAD) and reveal the relevant molecular mechanism. To this end, we manipulated the expression of DYNLL1 and PRKN with shRNA and/or overexpression to assess their effects on A549 cell phenotypes including cell proliferation, cycle arrest and apoptosis using CCK-8 assay, EdU staining, colony formation assay, flow cytometry, TUNEL and western blot. DYNLL1 is a carcinogenic factor in LUAD since it is highly expressed and DYNLL1 upregulation is associated with the low overall survival rate of LUAD patients. Silencing DYNLL1 inhibited the proliferation of LUAD cells while accelerating cell cycle arrest and apoptosis. The regulatory effects of silencing DYNLL1 were counteracted by PRKN deficiency, indicating a functional connection between DYNLL1 and PRKN, which could be attributed to the ubiquitination of DYNLL1 by PRKN. This study could help identify the role of DYNLL1 in LUAD pathogenies and develop reliable therapeutic targets for LUAD improvement.